Effects of Papacarie on children with dental caries in primary teeth: a systematic review and meta‐analysis. Issue 4 (23rd April 2018) - Deng, Yuejia; Feng, Ge; Hu, Bo; Kuang, Yunchun; Song, Jinlin
Abstract : Background: Caries in primary teeth hinder the child to bite and chew and influence their development. Papacarie has the characteristics of selective removal of decayed tissue and can preserve healthy dentine to the maximum, but its efficiency has not been critically evaluated compared to conventional method. Aim: This review is aiming at comparing the Papacarie and traditional method in caries removal in primary dental caries with children. Design: Comprehensive literature searching at PubMed, Embase, Cochrane Central Register of Controlled Trials, and Web of Science to January 2018. Results: Six randomized controlled trials (RCTs) and four prospective controlled clinical trials (CCTs) were included. The microbiota in caries dentine was significantly reduced using the Papacarie treatment (MD = 0.57, 95% CI 0.04 to 1.09, P = 0.03), and the anxiety feeling declined more in the Papacarie group (MD = −1.01, 95% CI −1.72 to −0.30, P < 0.005). There was a greater 200.79 (MD = 200.79, 95%CI 152.50 to 249.09, P < 0.00001) increase in time taken for the Papacarie treatment compared with the conventional method. Conclusion: Papacarie exerts a positive effect in reducing the bacteria and decreases the pain during caries removal in primary teeth although it costed a longer treatment time compared with the conventional method.